Effect of 60Coγ ray irradiation on adhesion of LIE coatings. (2nd November 2017) - Liu, Ning; Xu, Guoyue; Guo, Tengchao; Meng, Xue; Tan, Shujuan
ABSTRACT: A new gamma-ray irradiation method was used to modify the inorganic silicate binder for improving the adhesion of low infrared emissivity (LIE) coatings. First, the spectral characteristic of the solidified irradiated inorganic silicate was characterised by FTIR and the cross-section morphology of the coatings was observed by SEM. Then, the adhesion of LIE coatings containing irradiated inorganic silicate was systematically investigated by the scratch test. In addition, the adhesion of coatings in high-temperature conditions was also studied. The results indicated that the LIE coatings could exhibit better adhesion after irradiated due to the Si–O–Fe chemical bonding. At last, the infrared emissivity of the LIE coatings at different temperature was measured by IR-2. The irradiated coatings still kept LIE and the lowest infrared emissivity (500°C) was 0.41.